Comparison of Indian BOMAB and ICRP voxel phantom for calibration of shadow shield whole body counter. (February 2022) - Manohari, M.; Sugumar, P.; Deepu, R.; Mathiyarasu, R.; Venkatraman, B.
Abstract: In-vivo whole body monitors are calibrated with various types of phantoms like Bottle Mannikin absorption phantom (BOMAB), IGOR phantom, Masonite cut sheet phantom, realistic numerical phantoms (NORMAN, ICRP voxel phantom). These phantoms contain either point sources, rod sources, uniform source or radionuclides distributed in soft tissues etc. In this study the efficiency values of Shadow Shield wholebody counter (SSC) for 137 Cs and 60 Co obtained theoretically using ICRP adult voxel male reference phantom (ICRP-AM) having sources distributed in soft tissues and muscles ICRP-AM(S) are compared with the measured efficiencies of Indian BOMAB phantom having mid axial source distribution (BOM-I(A)). The results show that the efficiency value of BOM-I(A) for 137 Cs and 60 Co is 30% and 20% lower respectively compared to that of ICRP-AM(S). This is due to the variation in size, composition and source distribution between the two phantoms. Study using Indian Voxel phantom shows that the increase in the size of ICRP-AM contributed to an increase of 14% for 137 Cs. In case of 60 Co the size did not have any influence. Uniform distribution has 9% and 17% higher efficiency than axial distribution for 137 Cs and 60 Co respectively as shown by the simulation study using uniformly filled Indian BOMAB phantom (BOM-I(U)). The actual tissue composition and source distribution in soft tissue as shown by Indian voxel has efficiencies 12–14% higher compared to BOM-I(U). The systemic error due to the axial source distribution is recognized and quantified to be 22–25% lower compared to that of a realistic phantom with radionuclides in soft tissue and muscle. This study has resulted in an efficiency of the system using Indian realistic Voxel phantom. The efficiencies are 0.65 CPS/kBq for 137 Cs and 0.49 CPS/kBq for 60 Co. Highlights: Monte Carlo modeling of Shadow shield counter scanning mode using multiple static locations. Comparison of calibration factors of SSC obtained using BOM-I(A) and ICRP-AM. Factors responsible for the deviation identified and their effect quantified. Studied numerically the effect of distribution using BOM-I(U). Studied the effect of size using Indian Voxel and ICRP-AM phantoms.